Mengenal Ulama Melalui Inskripsi Keagamaan (Studi Kasus di Martapura Kalimantan Selatan) - Ridwan Bustamam (Jurnal Lektur Keagamaan, 2012)
This article is the result of the research on religious inscriptions around Martapura, South Kalimantan in 2012. Although similar research has been conducted there before, but it still rarely used religious archaeological perspective. Based on tracking data, it turns out quite a lot of Islamic inscriptions in the area. The study is limited to objects that are considered the most prominent ones, they are: the Tomb of Sheikh Muhammad Al-Banjari Arsyad, Tomb of Sheikh Abdul Hamid Abulung, Al-Karomah Great Mosque, and the Mosque of Sheikh Abdul Hamid Abulung. In general, the inscriptions found are written in Arabic language and Arabic sript, as well as in the Malay language and Jawi script, both of which are original and duplicated. The content of inscriptions include historical facts about the existence of prominent scholars. Reference text inscriptions are generally taken from the verse of the Qur'an or Hadith. This research will lead readers to uncover the deeper meaning of the text on the inscription, the influence of the thinking of the author of the text, and even trace the history of the Sultanate of Banjar that is being reconstructed.